Betting on a new idea [organic LEDs]. - Savage, P.R.
The author discusses how a model collaboration between Universal Display Corp. and Princeton University is taking cutting-edge organic LEDs from lab to market.
Keywords: LED displays; Enabling technology; Flexible displays; Manufacturing processes; Model collaboration; Organic LED; State-of-the-art technology; Symbiotic success